Drilling – Equipment, Methods and Materials - Laboratory Studies of Formation Damage in Sands Con... - H. J. Hilll; A. E. Anderson (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
Laboratory data for 155 field muds and 77 .shales have been used to develop correlations to estimate the net streaming potential component of the SP. Analysis of these data and comparison with field tests show that streaming potential corrections must be made to obtain an accurate estimate of the electrochemical potential for use in the determinntion of formation water resi-iiviy. The self-potential curve is related to formation water resistivity, and considerable effort within the oil industry has been directed toward clarifying this relationship. The Schlumbergers and Leonardon1,2 recognized that two types of potentials, electrochemical and electro-kinetic, resulted in the net potential variation in the borehole. Most of the later papers have dealt with the electrochemical component and its controlling parameters. The investigations of Wyllie,2" Salisch' and Moore5 provide the most extensive sources of data on streaming potentials across mud cakes. These authors observed streaming potentials of sufficient magnitude to be of critical importance in SP interpretation, if it is assumed that streaming potentials develop only opposite permeable beds. Streaming potentials across shales have been reported by Schenck and by Gondouin, et al.7 Since SP magnitude is the difference in potential opposite shale and sand beds, these authors suggested that the net streaming potential component may be negligible. The present investigation was initiated to evaluate empirically some of the parameters controlling the magnitude of the net borehole streaming potential and to determine whether useful relations between mud properties and net streaming potential could be established. Field muds were used in this investigation. These muds were characterized by the amount and type of chemical treatment utilized for five days before Sampling. Filter loss, mud resistivity, mud density and filtrate resistivity were determined for each mud with conventional methods and apparatus. Mud filtrate pH was estimated with Hydrion pH paper for the appropriate range. Streaming PotentIals Across MuD Cakes Commercial calomel-saturated KC1 electrodes are subject to potential changes attributed to contamination of the very small fiber-tip bridge by particles of clay from the drilling mud.3 To minimize this difficulty, a large diameter bridge (Fig. 1) was constructed with saturated KC1-agar gel and a filter disc of microporous porcelain. Experiments showed that streaming potentials across this bridge are less than 0.2 mv at pressure dif-